Review Of Vicharchika And Its Management Through Ayurveda (International Journal of Environmental Sciences, 2025)
Vicharchika, classified as a KshudraKushta in Ayurveda, is a chronic skin disorder characterized by itching, discharge, eruptions, and dark discoloration. Its clinical presentation closely parallels eczema (atopic dermatitis) in modern dermatology. Contemporary management relies mainly on topical corticosteroids and immunosuppressants, which offer symptomatic relief but carry risks of adverse effects and recurrence. Ayurveda advocates Shodhana (purification) and Shamana (palliative) therapies to eliminate vitiated Doshas and restore systemic balance. This review highlights the similarities in presentation, differences in management approaches, and the potential benefits of integrating Ayurvedic principles with modern dermatological care.